Decompressive craniectomy: Comparative analysis between surgical time and better prognosis - Bem Junior, Luiz Severo; Silva, Ana Cristina Veiga; Menezes, Marcelo Diniz de; Galvão, Maria Júlia Tabosa de Carvalho; Ferreira Neto, Otávio da Cunha; Alencar Neto, Joaquim Fechine de; Rabelo, Nicollas Nunes; Almeida, Nivaldo Sena; Valença, Marcelo Moraes; Azevedo Filho, Hildo Rocha Cirne de (Frontiers in Neurology, 2022)
Background: Malignant ischemic stroke is characterized by the involvement of ⅔ of the area of the middle cerebral artery, associated with cerebral edema, intracranial hypertension (ICH) and cerebral herniation, generating high morbidity and mortality. Over the years, several therapies have been studied in an attempt to reverse or reduce the damage caused by this vascular disorder, including decompressive craniectomy (DC), a surgical technique reserved for cases that evolve with refractory ICH. Methods: This study seeks to perform a comparative analysis on the effectiveness of decompressive craniectomy using four randomized clinical trials and the results found in the retrospective study by Bem Junior et al [1]. Results: The total sample consisted of 263 patients, among which 118 were randomized and 145 were part of the retrospective study. The outcome was analyzed based on the modified Rankin Scale (mRS) for 6 and 12 months. The mean time to perform the DC was 28.4 hours in the randomized trials, with the late approach (> 24 hours) associated with unfavorable outcomes (mRS between 4 and 6). Conclusion: Compared to the aforementioned studies, the study by Bem Junior et al. shows that a surgical approach in less than 12 hours had a better outcome, with 70% of the patients treated early classified as mRS 2 and 3 at the end of 12 months [1]. Decompressive craniectomy is currently the most effective measure to control refractory ICH in cases of malignant ischemic stroke, and the most appropriate approach before surgery is essential for a better prognosis for patients.